2013
DOI: 10.1080/20445911.2013.799170
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the consequences of bilingualism for language processing and cognition

Abstract: Contemporary research on bilingualism has been framed by two major discoveries. In the realm of language processing, studies of comprehension and production show that bilinguals activate information about both languages when using one language alone. Parallel activation of the two languages has been demonstrated for highly proficient bilinguals as well as second language learners and appears to be present even when distinct properties of the languages themselves might be sufficient to bias attention towards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
393
2
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 523 publications
(418 citation statements)
references
References 92 publications
15
393
2
8
Order By: Relevance
“…There is reason to expect bilingualism to correlate with performance on at least some types of EF tasks (e.g., Kroll & Bialystok, 2013), however, bilingual and monolingual participants in this sample did not differ on any EF scores (all |t|s < 1). 5 Bilinguals have sometimes been shown to outperform monolinguals on both incongruent and congruent trials on inhibitory tasks (thus showing no advantage in inhibition difference scores; e.g., Costa, Hernández, Costa-Faidella, & Sebastián-Gallés, 2009), however bilinguals in this sample performed no differently from monolinguals on either incongruent or congruent trials in the auditory or visual inhibition tasks (all |t|s < 1.34).…”
Section: Musical Experience Ability and Domains Of Efmentioning
confidence: 68%
“…There is reason to expect bilingualism to correlate with performance on at least some types of EF tasks (e.g., Kroll & Bialystok, 2013), however, bilingual and monolingual participants in this sample did not differ on any EF scores (all |t|s < 1). 5 Bilinguals have sometimes been shown to outperform monolinguals on both incongruent and congruent trials on inhibitory tasks (thus showing no advantage in inhibition difference scores; e.g., Costa, Hernández, Costa-Faidella, & Sebastián-Gallés, 2009), however bilinguals in this sample performed no differently from monolinguals on either incongruent or congruent trials in the auditory or visual inhibition tasks (all |t|s < 1.34).…”
Section: Musical Experience Ability and Domains Of Efmentioning
confidence: 68%
“…Furthermore, as shown by Paap & Greenberg (2013), tasks typically used to explore some of these components of executive control (e.g. inhibition) do not correlate with each other, pointing to the multidimensional nature of the measures obtained (see also Kroll & Bialystok, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…At a broad level, the underlying hypothesis for the so-called 'bilingual advantage' in executive functions is that bilinguals are used to constantly dealing with different languages and to preventing mutual interference between languages by selecting the target language while inhibiting the non-target language(s). This practice provides bilinguals with a somewhat enhanced mental flexibility, which results in augmented or improved skills related to the management of conflicting information as compared to monolinguals (see Kroll & Bialystok, 2013, for a review). In other words, speaking several languages can lead to benefits that go beyond the realm of language, impacting on global cognitive functioning and, more specifically, on the mechanisms responsible for selecting one language while managing interference from the other(s).…”
Section: Introductionmentioning
confidence: 99%
“…Being able to restrict language processing to only the target language would seem to be very useful, given that there is a considerable amount of evidence that in lexical access, words from both a bilingual's languages become active (for recent reviews see Kroll & Bialystok, 2013). In the domain of visual word recognition, for instance, many studies have shown differences in the processing of words that are identical or similar in a bilingual's two languages (e.g., cognates such as Dutch and English ring, and interlingual homographs such as list, meaning trick in Dutch), as compared to words without any overlap in form.…”
Section: Bilingual Language Processing Is Language Non-selectivementioning
confidence: 99%